1997
DOI: 10.1177/107110079701800708
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment of Anterior Ankle Impingement

Abstract: Ankle arthroscopy has recently allowed the elaboration of less invasive techniques for the treatment of anterior impingement. Its indications, advantages, and drawbacks in this application are discussed. Between 1987 and 1994, 133 patients were treated for ankle impingement. Among them, 58 patients, 37 men and 21 women (mean age, 28.5 years), who had failed a trial of conservative treatment were treated by means of tibiotalar arthroscopy. Twenty-seven were athletes engaged in sports with abnormal stressing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 14 publications
0
43
0
2
Order By: Relevance
“…Branca et al 2 clarified the results of arthroscopic treatment of AIE according to Scranton's classification, and found the best results are obtained in stage I and II. In stage III and IV, where the damage was extensive, there were recurrences of the osteophytes, probably resulting from insufficient removal of the tibial and talar osteophytes and from degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Branca et al 2 clarified the results of arthroscopic treatment of AIE according to Scranton's classification, and found the best results are obtained in stage I and II. In stage III and IV, where the damage was extensive, there were recurrences of the osteophytes, probably resulting from insufficient removal of the tibial and talar osteophytes and from degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In some people they cause anterior ankle pain and limit dorsiflexion of the ankle during activity. The symptoms caused by osteophytes are variously called athlete's ankle, 8 footballer's ankle, 7 anterior ankle impingement, 2,11,12,14,18 anterior tibiotalar spur, 15 anterior ankle osteophytes, 3 or anterior impingement exostosis (AIE). 10,13,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Even though in the literature, some investigators have reported technical difficulties in addressing posteromedial lesions and in performing posterior ankle synovectomy [6, 7], we have not experienced this problem, using the 2-portal endoscopic hindfoot technique [4, 8]. In most cases chronic anterior ankle pain is caused by an anterior impingement syndrome, tibiotalar anterior osteophytes, intra-articular foreign bodies, local synovitis, or osteochondral defects [9]. These conditions will markedly reduce ankle function especially limiting dorsiflexion due to an anterior impediment and capsular contracture [9].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases chronic anterior ankle pain is caused by an anterior impingement syndrome, tibiotalar anterior osteophytes, intra-articular foreign bodies, local synovitis, or osteochondral defects [9]. These conditions will markedly reduce ankle function especially limiting dorsiflexion due to an anterior impediment and capsular contracture [9]. Anterior ankle joint pathology can be treated by means of an anterior ankle arthroscopy [10].…”
Section: Discussionmentioning
confidence: 99%
“…Die Mehrzahl der Untersucher bestätigt jedoch eine positive Korrelation zwischen Langzeitergebnis und begleitender Knorpelläsion [5,11,22,24].…”
Section: Materials Und Methodeunclassified